2022
DOI: 10.1186/s40352-021-00162-6
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of post-release programs for women exiting prison with substance-use disorders: assessing current programs and weighing the evidence

Abstract: Background The rising rates of women in prison is a serious public health issue. Unlike men, women in prison are characterised by significant histories of trauma, poor mental health, and high rates of substance use disorders (SUDs). Recidivism rates of women have also increased exponentially in the last decade, with substance related offences being the most imprisoned offence worldwide. There is a lack of evidence of the effectiveness of post-release programs for women. The aim of this systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 65 publications
(283 reference statements)
0
9
0
Order By: Relevance
“…Similarly, a recent review of post‐release programs for women with substance use problems reported that of 12 programs involving 3799 women, only five were associated with a significant reduction in recidivism, and only one was associated with a significant reduction in substance use [ 44 ]. The authors concluded that women in prison with substance use problems benefit most from continuity of care from prison to the community and that such care must incorporate gender‐responsive programming and individualised case management to target comorbid mental health and substance use problems [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent review of post‐release programs for women with substance use problems reported that of 12 programs involving 3799 women, only five were associated with a significant reduction in recidivism, and only one was associated with a significant reduction in substance use [ 44 ]. The authors concluded that women in prison with substance use problems benefit most from continuity of care from prison to the community and that such care must incorporate gender‐responsive programming and individualised case management to target comorbid mental health and substance use problems [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…While not independently predicting future violence it manifests through related risk factors ( 46 ). This seems to be particularly true for the present population of patients with SUD as substance abuse frequently serves to cope with symptoms of other mental health issues ( 47 ). Hence, our findings should not be construed as diminishing the relevance of this clinical factor.…”
Section: Discussionmentioning
confidence: 99%
“…It is often reported by women in prison that experiences of trauma and mental illness precede substance-use, with women reportedly using substances to alleviate distress associated with trauma and to manage mental health issues [ 13 , 14 , 19 ]. Mental health and substance-use are therefore interrelated and complex health issues that not only increase a woman’s risk of imprisonment [ 36 , 37 ] but may also impact women’s integration into the community post-release, and therefore reimprisonment.…”
Section: Introductionmentioning
confidence: 99%